Tumor burden, inflammation, and product attributes determine outcomes of axicabtagene ciloleucel in large B-cell lymphoma - Locke, Frederick L.; Rossi, John M.; Neelapu, Sattva S.; Jacobson, Caron A.; Miklos, David B.; Ghobadi, Armin; Oluwole, Olalekan O.; Reagan, Patrick M.; Lekakis, Lazaros J.; Lin, Yi; Sherman, Marika; Better, Marc; et al. (Blood advances, 2020)
ZUMA-1 demonstrated a high rate of durable response and a manageable safety profile with axicabtagene ciloleucel (axi-cel), an anti-CD19 chimeric antigen receptor (CAR) T-cell therapy, in patients with refractory large B-cell lymphoma. As previously reported, prespecified clinical covariates for secondary end point analysis were not clearly predictive of efficacy; these included Eastern Cooperative Oncology Group performance status (0 vs 1), age, disease subtype, disease stage, and International Prognostic Index score. We interrogated covariates included in the statistical analysis plan and an extensive panel of biomarkers according to an expanded translational biomarker plan. Univariable and multivariable analyses indicated that rapid CAR T-cell expansion commensurate with pretreatment tumor burden (influenced by product T-cell fitness), the number of CD8 and CCR7+CD45RA+ T cells infused, and host systemic inflammation, were the most significant determining factors for durable response. Key parameters differentially associated with clinical efficacy and toxicities, with both theoretical and practical implications for optimizing CAR T-cell therapy. This trial was registered at www.clinicaltrials.gov as #NCT02348216. •Axi-cel durable responses were associated with low baseline tumor burden, low systemic inflammation, and high product CCR7+CD45RA+ T cells.•Distinct sets of factors associated with durable response, grade ≥3 cytokine release syndrome, and grade ≥3 neurologic events. [Display omitted]